S-palmitoylation regulates AMPA receptors trafficking and function: a novel insight into synaptic regulation and therapeutics - Jun Han; Pengfei Wu; Fang Wang; Jianguo Chen (Elsevier, 2015)
Glutamate acting on AMPA-type ionotropic glutamate receptor (AMPAR) mediates the majority of fast excitatory synaptic transmission in the mammalian central nervous system. Dynamic regulation of AMPAR by post-translational modifications is one of the key elements that allow the nervous system to adapt to environment stimulations. S-palmitoylation, an important lipid modification by post-translational addition of a long-chain fatty acid to a cysteine residue, regulates AMPA receptor trafficking, which dynamically affects multiple fundamental brain functions, such as learning and memory. In vivo, S-palmitoylation is controlled by palmitoyl acyl transferases and palmitoyl thioesterases. In this review, we highlight advances in the mechanisms for dynamic AMPA receptors palmitoylation, and discuss how palmitoylation affects AMPA receptors function at synapses in recent years. Pharmacological regulation of S-palmitoylation may serve as a novel therapeutic strategy for neurobiological diseases.